탄소나노튜브 방향성 수축 전송 방법이 CNTFET 기반 회로 성능에 미치는 영향에 관한 연구 - 조근호; Cho, Geunho (Journal of the convergence on culture technology : JCCT, 2018)
The CNTFET, which is attracting attention as a next-generation semiconductor device, can obtain ballistic or near-ballistic transport at a lower voltage than that of conventional MOSFETs by depositing CNTs between the source and drain of the device. In order to increase the performance of the CNTFET, a large number of CNTs must be deposited at a high density in the CNTFET. Thus, various manufacturing processes to increase the density of the CNTs have been developed. Recently, the Directional Shrinking Transfer Method was developed and showed that the current density of the CNTFET device could be increased up to 150 uA/um. So, this method enhances the possibility of implementing a CNTFET-based integrated circuit. In this paper, we will discuss how to evaluate the performance of the CNTFET device compared to a MOSFET at the circuit level when the CNTFET is fabricated by the Directional Shrinkage Transfer Method. 차세대 반도체 소자로 관심을 받고 있는 CNTFET은 소자의 소스와 드레인 사이에 CNT를 배치시켜, 기존 MOSFET보다 작은 전압으로 전자의 ballstic 혹은 near-ballastic 이동을 가능하게 만든 반도체 소자이다. CNTFET의 성능을 높이기 위해서는 많은 수의 CNT를 CNTFET 안에 높은 밀도로 배치해야 하기 때문에 CNT의 밀도를 증가시키기 위한 다양한 공정들이 개발되고 있다. 최근, 방향성 수축 전송 방법이 개발되어 CNTFET의 전류 밀도를 150uA/um까지 향상시켜줄 수 있음을 보이고 있어, CNTFET 기반 집적회로의 구현 가능성을 높이고 있다. 본 논문에서는, 방향성 수축 전송 방법으로 CNTFET 소자를 만들 경우, CNTFET 회로의 성능이 기존 MOSFET의 성능에 비해 얼마나 향상시킬 수 있는지 그 성능을 평가할 수 있는 방안을 논의하고자 한다.